2020
DOI: 10.1007/s00300-020-02731-1
|View full text |Cite
|
Sign up to set email alerts
|

Microbial insights from Antarctic and Mediterranean shallow-water bone-eating worms

Abstract: Bone-eating worms of the genus Osedax (Annelida, Siboglinidae) form unique holobionts (functional entity comprising host and associated microbiota), highly adapted to inhabit bone tissue of marine vertebrates. These gutless worms have developed nutritional symbioses housing intracellular, horizontally acquired, heterotrophic bacteria hypothesised to harness nutrients from organic compounds, sequestered within the bone. Despite previous efforts, critical mechanisms mediating activity and acquisition of diverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 75 publications
(163 reference statements)
0
12
0
Order By: Relevance
“…Metagenomic assembly, binning, taxonomic identification, ORF prediction, and annotation. For each sample type (Osedax mucofloris and bone surface biofilm communities), the quality-filtered metagenomic reads (Trimmomatic version 0.36) were coassembled with SPAdes v3.12 (94) for kmers 21,33,55,77, and 99, with the metaSPAdes-assembler option enabled (see Table S1 in the supplemental material for read counts). Binning was conducted on the resulting assemblies using the MetaWRAP pipeline (version 1.0.1) (95).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metagenomic assembly, binning, taxonomic identification, ORF prediction, and annotation. For each sample type (Osedax mucofloris and bone surface biofilm communities), the quality-filtered metagenomic reads (Trimmomatic version 0.36) were coassembled with SPAdes v3.12 (94) for kmers 21,33,55,77, and 99, with the metaSPAdes-assembler option enabled (see Table S1 in the supplemental material for read counts). Binning was conducted on the resulting assemblies using the MetaWRAP pipeline (version 1.0.1) (95).…”
Section: Methodsmentioning
confidence: 99%
“…To date, only a few studies have been published that focus on microbial communities to understand the necessary complex interactions in bone degradation, mainly relying on 16S rRNA gene sequencing data (30)(31)(32)(33) and one metagenomic study of a whale fall (34). We here provide a first comprehensive overview and identify putative key functions involved in bone degradation of the marine bone microbiome retrieved from deployed bone material, including microbial communities from the gutless worm Osedax mucofloris and free-living microbial assemblages developing on the bone surface.…”
mentioning
confidence: 99%
“…Polaribacter species have been isolated from Antarctic soil and in biofilms on stones from the North Sea (Choo et al, 2020 ; Kim et al, 2013 ), and the genus was detected in the intestine of marine organisms and algae (Hyun et al, 2014 ; Nedashkovskaya et al, 2013 ; Wei et al, 2018 ). Alkalimarinus sediminis was isolated from marine sediment in Shandong Province, China (Zhao et al, 2015 ), and Alkalimarinus species were found in bone‐eating worms ( Osedax mediterranea ) from the Mediterranean Sea (Hewitt et al, 2020 ). Healthy and diseased Dentex and Sparus aurata (bony fishes) cultured in Spanish Mediterranean aquaculture contained Enterovibrio coralii strains and possibly Enterovibrio nigricans (Pascual et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Two relevant such sources are the microbial biofilms that develop on the surface of bones from shallow and deep water marine environments, and the symbionts of bone-dwelling worms, e.g., Osedax mucofloris . These bio-resources have been shown to have a wide microbial diversity, whose compositions and involvement in the various and successive events involved in the degradation of mature bone, have been investigated to some detail [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] . In this process, recent metagenome sequence analyses suggested that, as mentioned above, the acidification by some organisms is key before the hydrolysis of bone matrix is initiated by other community members [27] .…”
Section: Introductionmentioning
confidence: 99%